2021
DOI: 10.1002/anie.202114089
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Reaction Dynamics and Size Change during the Photomechanical Transformation of 9‐Methylanthracene Single Crystals

Abstract: Photomechanical molecular crystals that expand under illumination could potentially be used as photonpowered actuators.I nt his study,w ef ind that the use of highquality single crystals of 9-methylanthracene (9MA)l eads to more homogeneous reaction kinetics than that previously seen for polycrystalline samples,p resumably due to al ower concentration of defects.F urthermore,s imultaneous observation of absorbance and shape changes in single crystals revealed that the dimensional change mirrors the reaction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…As can be seen, it showed a sigmoidal curve, suggesting that the photopolymerization reaction proceeds heterogeneously on molecular scale. This is very similar to the case of 9MA crystals, indicating that the presence of the photoproduct accelerated the next photoreactions of neighboring molecules 22 .…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…As can be seen, it showed a sigmoidal curve, suggesting that the photopolymerization reaction proceeds heterogeneously on molecular scale. This is very similar to the case of 9MA crystals, indicating that the presence of the photoproduct accelerated the next photoreactions of neighboring molecules 22 .…”
Section: Introductionsupporting
confidence: 75%
“…Furthermore, we focused on the change in the birefringence associated with the photopolymerization reaction. The birefringence change is very sensitive to the photochemical reactions and the change is proportional to the conversion in the photochemical reactions 22,27,28 .…”
Section: Change In Birefringence During Photochemical Reaction In Sin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first example of the large photomechanical expansion of organic molecular crystals was reported by Bardeen et al, who observed an average 8% expansion of 9- tert -butyl-anthracene ester (9TBAE) nanorods . Subsequent studies suggested that the 9TBAE nanorod expansion did not result from the molecular volume change but instead resulted from the rearrangement of molecular contents. , Recent studies have shown that molecular orientation is coherently correlated with photomechanical behavior and photochemical dynamics. , For our ( E )- NAAM hollow microcrystals, the significant molecular geometry and structural changes from parallel stacking monomeric pairs to butterfly-like photodimers satisfy the first prerequisite for expansion (Figure S19). Although there was no direct comparison between the crystal volume of the monomer and the photoreacted dimer, the formation of the highly distorted photodimer suggests that the crystal lattice might have experienced expansion during photodimerization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From the perspective of crystal morphology, it seems that the unique hollow crystal structure is essential for such unusual expansion, as it leaves more void space for molecules to extend and distort. It has been reported that a neat single crystal would lead to more homogenous reaction kinetics than polycrystalline samples due to a lower concentration of defects . However, the unique interior cavities of ( E )- NAAM single crystals may help create an environment of high concentration of “defects”.…”
Section: Results and Discussionmentioning
confidence: 99%